Erica Ollmann Saphire: How the Study of HIV and Other Viruses Informed the Rapid Development of Vaccines and Therapeutic Antibodies Against COVID-19 - Neil S. Greenspan (Case Western Reserve University, 2022)
Neil Greenspan, professor of pathology at Case Western Reserve University and senior editor at Pathogens and Immunity talks with Erica Ollmann Saphire, President and Chief Executive Officer of the La Jolla Institute for Immunology, about her work on hemorrhagic fever viruses and SARS-CoV-2. She'll be speaking about these topics at the Keystone Symposium, Lessons from the Pandemic: Responding to Emerging Zoonotic Viral Diseases. Dr. Sapphire is an eminent structural biologist devoted to understanding viral pathogens and pathogenesis.